2019
DOI: 10.1111/exd.13908
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of inflammatory cytokines and chemokines in lipopolysaccharide‐stimulated melanocytes from lightly and darkly pigmented skin

Abstract: Increasing evidence suggests that human epidermal melanocytes play an important role in the skin immune system; however, a role of their pigmentation in immune and inflammatory responses is poorly examined. In the study, the expression of Toll‐like receptor 4 (TLR4) and inflammatory cytokines and chemokines by cultured normal melanocytes derived from lightly and darkly pigmented skin was investigated after cell stimulation with lipopolysaccharide (LPS). The basal TLR4 mRNA level in heavily pigmented cells was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 81 publications
0
26
0
Order By: Relevance
“…It has been reported that the melanin pigment itself may play a role in controlling the immune response. Compared to melanocytes that contain a large amount of melanin, melanocytes containing little melanin produce a higher number of cytokines such as IL-6 and IL-10 [41,42]. l-DOPA, the intermediate product of melanin synthesis, and its oxidation products function as potent immunosuppressive agents that inhibit lymphocyte proliferation and abrogate inflammatory cytokine production by activated lymphocytes [41,42].…”
Section: Melanin and Inflammatory Responsesmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that the melanin pigment itself may play a role in controlling the immune response. Compared to melanocytes that contain a large amount of melanin, melanocytes containing little melanin produce a higher number of cytokines such as IL-6 and IL-10 [41,42]. l-DOPA, the intermediate product of melanin synthesis, and its oxidation products function as potent immunosuppressive agents that inhibit lymphocyte proliferation and abrogate inflammatory cytokine production by activated lymphocytes [41,42].…”
Section: Melanin and Inflammatory Responsesmentioning
confidence: 99%
“…Compared to melanocytes that contain a large amount of melanin, melanocytes containing little melanin produce a higher number of cytokines such as IL-6 and IL-10 [41,42]. l-DOPA, the intermediate product of melanin synthesis, and its oxidation products function as potent immunosuppressive agents that inhibit lymphocyte proliferation and abrogate inflammatory cytokine production by activated lymphocytes [41,42]. Mohagheghpour et al have shown that non-toxic concentrations of synthetic melanin suppress the production of cytokines such as TNF, IL-1β, IL-6, and IL-10 by reducing the efficiency of mRNA translation [43].…”
Section: Melanin and Inflammatory Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not surprising, considering that humans and rodents are separated by an estimated 96 million years of evolution 21 . Addressing this fact, many studies are being conducted on patient‐derived primary skin cells, including human keratinocytes, 22‐25 melanocytes, 26‐30 fibroblasts 31‐34 and cell co‐cultures 35‐37 . However, typical in vitro culture conditions fail to replicate and, in fact, do not come close to imitating the biomechanical and biochemical complexity of the microenvironment in which cells exist and to which they respond to in native tissues.…”
Section: Bridging the Gap Between “Simplicity” Of In Vitro And Complementioning
confidence: 99%
“…Previous reports indicated that LPS stimulation of epidermal (skin) melanocytes may increase pigmentation (Ahn et al, 2008;Tam et al, 2019). We therefore explored the expression of melanogenesis-related genes including MLANA, TYR, TYRP1 and PMEL, melanocyte-inducing transcription factor (MITF), dopachrome tautomerase (DCT) and melanocortin receptor 1 (MC1R) (reviewed by D'Mello et al, 2016), but found no differential expression of these genes after LPS stimulation (Figure 4a) and no visible change in HCM pigmentation (Figure 4b) within the timeframe of our experiments.…”
Section: Transcriptomic Changes Induced By Lps Stimulation and Functional Annotationmentioning
confidence: 99%